Design, Synthesis and In Vitro Antiproliferative Activity of Novel Isatin‐Quinazoline Hybrids. Issue 2 (February 2015) - Fares, Mohamed; Eldehna, Wagdy M.; Abou‐Seri, Sahar M.; Abdel‐Aziz, Hatem A.; Aly, Mohamed H.; Tolba, Mai F.
<x xml:space="preserve">Abstract</x> Using a molecular hybridization approach, a new series of isatin‐quinazoline hybrids 15a–o was designed and synthesized via two different synthetic routes. The target compounds 15a–o were prepared by the reaction of quinazoline hydrazines 12a–e with indoline‐2, 3‐diones 13a–c or by treating 4‐chloroquinazoline derivatives 11a–e with isatin hydrazones 14a–c. The in vitro anticancer activity of the newly synthesized hybrids was evaluated against the liver HepG2, breast MCF‐7 and colon HT‐29 cancer cell lines. A distinctive selective growth inhibitory effect was observed towards the HepG2 cancer cell line. Compounds 15b, 15g and 15l displayed the highest potency, with IC50 values ranging from 1.0 ± 0.2 to 2.4 ± 0.4 μM, and they were able to induce apoptosis in HepG2 cells, as evidenced by enhanced expression of the pro‐apoptotic protein Bax and reduced expression of the anti‐apoptotic protein Bcl‐2, in addition to increased caspase‐3 levels.